Effect of multiscale structure on the gas barrier properties of poly(lactic acid)/Ag nanocomposite films. (7th April 2019) - Fan, Chunli; Chi, Hai; Zhang, Cheng; Cui, Rui; Lu, Wangwei; Yuan, Minglong; Qin, Yuyue
Abstract : Poly(lactic acid) (PLA) is the most suitable for biodegradable packaging film because of its excellent integrated property, but the poor gas barrier property is its weakness. In this study, a nanocomposite film based on PLA incorporated with 0‐, 1‐, 3‐, 5‐, 10‐, or 15‐wt% nano‐Ag was developed. Effect of multiscale structure on the barrier properties of PLA/nano‐Ag films was studied. The PLA nanocomposite film with 5‐wt% nano‐Ag had the lowest water vapor permeability (WVP) value. Oxygen transmission rate (OTR) value for PLA nanocomposites with 3‐wt% nano‐Ag was found to be the lowest among all the samples. Multiscale structure was demonstrated by the scanning electron microscopy, Fourier transform‐infrared spectroscopy, X‐ray diffraction measurement, and differential scanning calorimetry results. The crystallinity of the PLA phase increased with the content of nano‐Ag in the PLA composites. The evolution of the PLA phase crystallinity could improve the barrier properties of PLA/nano‐Ag composite films for food packaging applications. From the view of multiscale structure, it is better to achieve a balance among short‐range conformation in the amorphous region, long‐range‐ordered structure, and ordered aggregated structure to improve the barrier properties of PLA/nano‐Ag composite films.